ASSOCIATED DEMOGRAPHIC CHARACTERISTICS OF ACNE RECURRENCE IN SEVERE ACNE PATIENTS TREATED WITH ORAL ISOTRETINOIN - Vũ Nguyệt, Minh; Phạm Diễm, Hương; Trần Thị, Quyên (Tạp chí Da liễu học Việt Nam, 2023)
Objectives: To investigate the relationship between the recurrence rate of acne treated with oral isotretinoin and some demographic characteristics. Methods: A retrospective, prospective study of 60 severe acne patients treated with isotretinoin divided into 2 groups based on cumulative dosing (60mg/kg and 120mg/kg). Recurrence was defined as the reappearance of grade 1 acne lesions according to Investigator’s Global Assessment (IGA) classification (FDA 2005) with at least 10 comedones or grade 2 or higher (at least 2 papules, pustules, or at least one nodule or cyst). Results: The mean age of the participants was 27.3 years old, 88.3% were female and the mean disease duration was 14.6 months. At the 12 month follow-up, 63.3% of patients in the study experienced relapse. The group of patients aged 18 - 29 had a recurrence rate of 71.4%, which was 1.6 times higher than the group of patients over 29 years old (44.4%); the difference was statistically significant (p < 0.05). When evaluated according to other demographic characteristics, the result showed that there was no association between the recurrence rate with gender, body mass index, disease duration, and maintenance therapy. Conclusion: The relapse rate was higher in younger patients (age 18 - 29 years). There was no association between the recurrence rate with gender, body mass index, disease duration, and maintenance therapy. Received: 01/04/2022 Revised: 10/05/2022 Accepted: 18/05/2022